(untitled) - Slesinger, Jan; David, Andrej; Sosedova, Jarmila (Doprava a spoje, 2012)
The analysis of the reasons for the formation of River Information Services (RIS). The functional arrangement for the system of fluvial informative services with using telematics. The characteristics of the chief telematics system parts. State with application and utilization of the system River Information Services in Slovakia. Model scenarios of practical situation on utilized application technology of system RIS in the cooperation within simulator Shipmaster P60